The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2337/db14-1603
|View full text |Cite
|
Sign up to set email alerts
|

HDL Cholesterol and Risk of Type 2 Diabetes: A Mendelian Randomization Study

Abstract: Observationally, low levels of HDL cholesterol are consistently associated with increased risk of type 2 diabetes. Therefore, plasma HDL cholesterol increasing has been suggested as a novel therapeutic option to reduce the risk of type 2 diabetes. Whether levels of HDL cholesterol are causally associated with type 2 diabetes is unknown. In a prospective study of the general population (n = 47,627), we tested whether HDL cholesterol-related genetic variants were associated with low HDL cholesterol levels and, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 26 publications
9
90
0
Order By: Relevance
“…The previous point can be further strengthened by running Mendelian randomization studies, something that has been used in DM. 16 Mendelian randomization studies establish causal relationship by comparing 2 groups of individuals with and without a genetic marker known to influence the variable being studied. As genotype assignment is random and not subject to confounding typically found in epidemiological studies, a higher prevalence of disease in the group with the marker implies causality.…”
Section: Resultsmentioning
confidence: 99%
“…The previous point can be further strengthened by running Mendelian randomization studies, something that has been used in DM. 16 Mendelian randomization studies establish causal relationship by comparing 2 groups of individuals with and without a genetic marker known to influence the variable being studied. As genotype assignment is random and not subject to confounding typically found in epidemiological studies, a higher prevalence of disease in the group with the marker implies causality.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, genetically determined increases in cholesterol specifically on large and extra-large HDL particles is associated with lower fasting glucose [37]. In contrast, an independent study showed no effect of HDL-cholesterol on diabetes risk [38]. …”
Section: Introductionmentioning
confidence: 99%
“…The data presented in Table 3 and Figure 3B indicated that HDL-C should not be considered as a substitute for ApoA1 in risk prediction for new T2DM. In addition to a growing body of evidence suggesting that HDL-C concentration does not accurately reflect the heterogeneous HDL particles and the HDL's vascular protective function [34,35], a recently published Mendelian randomization study [18] showed that low levels of HDL-C due to genetic variation do not increase risk of T2DM in the general population, which suggesting that the previously observed association between low levels of HDL-C and development of T2DM may be due to reverse causation of a state of prediabetes [18]. Similarly, a Mendelian randomization study showed that raised triglyceride levels were not causally associated with the risk of T2DM [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the most commonly identified risk factors for development of T2DM include older age [4], positive family history of diabetes [5], higher body mass index (BMI) [4], abdominal obesity [6], smoking [7], hypertension [8], higher fasting glucose level [9], physical inactivity [10] and metabolic syndrome [11]. There have been inconsistent reports on associations of ApoA1 and HDL-C with development of T2DM [12][13][14][15][16][17][18]. We examined the incidence of new T2DM over 4 years for association of clinical factors and lipids with development of T2DM among Chinese subjects who participated in a community-organized health checkout in both 2009 and 2013.…”
Section: Introductionmentioning
confidence: 99%